Oleanane and Stigmasterol-Type Triterpenoid Derivatives from the Stem Bark of Albizia gummifera and Their Antibacterial Activities - Tamrat Tesfaye Ayele; Getahun Tadesse Gurmessa; Zelalam Abdissa; Girmaye Kenasa; Negera Abdissa (Journal of Chemistry)
Chromatographic separation of methanol extract of stem bark of Albizia gummifera led to the isolation of two oleanane-type triterpenoids (1 and 2), a stigmasterol derivative (3), and stigmasterol (4). The structures of the compounds were elucidated based on 1D and 2D NMR spectroscopic data and comparing with reported literature values. The crude extract and the isolated compounds were evaluated for their antibacterial activities against five bacterial strains. Compounds 1, 2, and 4 showed marginal antibacterial activity with the growth inhibition zone ranging from 6.8 to 13.2 mm against the tested bacterial strains, with compounds 2 and 4 showing significant inhibition (13.0 and 13.2 mm) against S. flexneri and S. typhimurium, respectively. While, the standard drug, gentamycin showed inhibition zone 20.0 and 24.0 mm against S. flexneri and S. typhimurium, respectively.